White House launches AI Cyber Challenge to test how top AI models protect software (2023)
Today the Biden-Harris Administration launched a two-year competition that uses AI to protect the U.S.'s most critical software.
<标题>: 白宫启动人工智能网络挑战赛，测试顶级人工智能模型如何保护软件 Read_Status: New Read_Status_Date: 2026-01-26T11:33:53.530Z
Keywords: /unread